Binary SubtractionPublished on 24/2/2012 and last updated on 25/8/2018
Now we will discuss the process elaborately with the help of few examples. Suppose, A = 10101100 and B = 1010100 and we want to find out A - B. Now implementing the rules of binary subtraction The first step is 0 - 0 = 0 and that’s what is written in the place for result
Similarly again the last step is repeated as here the numbers are both 0 and from the table we know 0 - 0 = 0. From the table we can find out that 1 - 1 = 0 and it is written
The table shows that 1 - 0 = 1 and we have written exactly that in result Here 0 - 1 = 1 with borrowing of 1 from the next significant bit and that’s what has been done. We will treat the next 1 as 0 in the next step as shown below.
As the 1 was borrowed in the previous step we are treating the 1 as 0 and the result is 0 - 0 = 0 and that is written Again the last 1 has been borrowed because the operation done was 0 - 1 = 1 with borrow 1 from the next most significant bit and the final result of binary subtraction, we got is written in the place of result in the final step.